2017
DOI: 10.22161/ijeab/2.2.34
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trichoderma Fortified Compost on Disease Suppression, Growth and Yield of Chickpea

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…3). On the basis of the above statement, T8 was produced the maximum number of effective tiller/plant (3.49%) followed by T4 (3.40%), whereas the minimum value (2.07%) was given by T0 in 2016-2017. During 2017 were exhibited approximately equal performance with slight increase of effective tiller/plant.…”
Section: Effective Tiller/plantmentioning
confidence: 86%
“…3). On the basis of the above statement, T8 was produced the maximum number of effective tiller/plant (3.49%) followed by T4 (3.40%), whereas the minimum value (2.07%) was given by T0 in 2016-2017. During 2017 were exhibited approximately equal performance with slight increase of effective tiller/plant.…”
Section: Effective Tiller/plantmentioning
confidence: 86%
“…Talukdar et al [25] reported that poultry compost contains NH 4 -N and NO 3 -N (nitratenitrogen) readily taken by resident soil microorganisms that tend to exploit NH4+ more quickly than plants. Ammonia liberated with application of high nitrogen amendments kills soil-borne pathogens.…”
Section: Effect On Yieldmentioning
confidence: 99%
“…phaseoli, Rhizoctonia solani and Sclerotium rolfsii while applied with composts. Another field study showed that Trichoderma enriched compost reduced seedling mortality of chickpea and yield (Talukdar et al, 2017). However, information regarding biocontrol efficacy of Trichoderma species against soil borne bacterial crop diseases is limited.…”
Section: Introductionmentioning
confidence: 99%